The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/hbm.23947
|View full text |Cite
|
Sign up to set email alerts
|

Differences in white matter structure and cortical thickness between patients with traumatic and idiopathic chronic neck pain: Associations with cognition and pain modulation?

Abstract: Brain alterations are hypothesized to be present in patients with chronic whiplash-associated disorders (CWAD). The aim of this case-control study was to examine alterations in cortical thickness and white matter (WM) structure, and the presence of brain microhemorrhages in a patient group encountering chronic neck pain of traumatic origin (i.e., CWAD) when compared with a patient group characterized by nontraumatic chronic neck pain [i.e., chronic idiopathic neck pain (CINP)], and healthy controls. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 126 publications
(220 reference statements)
6
37
0
Order By: Relevance
“…First, images were visually inspected using the ExploreDTI quality assurance tools (e.g. looping of diffusion MRI images in differing image planes, inspection of outlier profiles and average residuals for diffusion weighted volumes) to allow for volumes with artefacts to be removed ( Coppieters et al, 2018 ; Ivers et al, 2018 ; Pijnenburg et al, 2016 ). Images were then corrected for subject motion and eddy current-induced geometric distortions in native space, with cubic interpolation and the RESTORE approach taken to maximize accuracy ( Chang et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, images were visually inspected using the ExploreDTI quality assurance tools (e.g. looping of diffusion MRI images in differing image planes, inspection of outlier profiles and average residuals for diffusion weighted volumes) to allow for volumes with artefacts to be removed ( Coppieters et al, 2018 ; Ivers et al, 2018 ; Pijnenburg et al, 2016 ). Images were then corrected for subject motion and eddy current-induced geometric distortions in native space, with cubic interpolation and the RESTORE approach taken to maximize accuracy ( Chang et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies focused on macrostructural alterations or clinical signs, but were unable to demonstrate findings of edema and/or lesions (Borchgrevink et al, 1997;Karlsborg et al, 1998). Two recent studies by Coppieters et al (2017Coppieters et al ( , 2018) assessed a restricted set of brain regions that were involved in pain processing and cognition. Two recent studies by Coppieters et al (2017Coppieters et al ( , 2018) assessed a restricted set of brain regions that were involved in pain processing and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Only in post-traumatic headache, subtle changes in the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC) were reported (Obermann et al, 2009). Two recent studies by Coppieters et al (2017Coppieters et al ( , 2018 assessed a restricted set of brain regions that were involved in pain processing and cognition. Their results showed a selective thinning in the left precuneus, together with a decrease in gray matter volume in the right superior parietal cortex and left cingulate cortex in patients with CINP compared to CWAD.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have demonstrated the presence of brain changes in chronic pain conditions, [17][18][19][20][21][22][23][24][25][26] only four studies were identified that investigated the effects of exercise on the brain. In these four studies, a large number of regions of interest (ROIs) were analysed, with increased activation in only two regions (insula, primary sensory motor cortex) reported by more than one study.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Reduced white and grey matter volume and density [17][18][19][20] have been demonstrated in people with chronic low back pain (LBP), 21 22 FM, 23 WAD 24 25 and nontraumatic neck pain. 24 Alterations in functional and structural connectivity between different brain areas have been shown in individuals with CRPS, 18 26 Finally, deficient inhibitory pain modulation in patients with WAD has been reported to correlate with cerebral metabolite levels. 27 Although the relationship is not well understood, some of these brain changes correlate with pain intensity, 28 29 and successful treatment of chronic pain has been associated with a reversal of abnormal brain morphometry.…”
Section: Introductionmentioning
confidence: 99%